2010
DOI: 10.4049/jimmunol.1002227
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: NLRP12 Controls Dendritic and Myeloid Cell Migration To Affect Contact Hypersensitivity

Abstract: Nucleotide-binding domain leucine rich repeat (NLR) proteins have emerged as fundamental regulators of inflammation and immunity. Although first described eight years, a physiologic role for NLRP12 has remained elusive until now. Here we describe a novel role for NLRs in inflammation by regulating immune cell migration. We find that murine Nlrp12, an NLR linked to atopic dermatitis and hereditary periodic fever in humans, is prominently expressed in dendritic cells (DCs) and neutrophils. Nlrp12-deficient mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(181 citation statements)
references
References 22 publications
9
168
1
3
Order By: Relevance
“…For instance, it has been shown that ASC and NLRP3 deficient mice display an impaired response to the skin sensitizers DNFB and TNCB (Watanabe et al, 2007). More recently, it was found that the LC of NLRP12 −/− mice exhibit defective migration to draining LN (Arthur et al, 2010). In this latter study, it was found also that NLRP12 deficiency attenuates the inflammatory response in two separate models of skin sensitization.…”
Section: The Integral Inflammasomesupporting
confidence: 58%
See 1 more Smart Citation
“…For instance, it has been shown that ASC and NLRP3 deficient mice display an impaired response to the skin sensitizers DNFB and TNCB (Watanabe et al, 2007). More recently, it was found that the LC of NLRP12 −/− mice exhibit defective migration to draining LN (Arthur et al, 2010). In this latter study, it was found also that NLRP12 deficiency attenuates the inflammatory response in two separate models of skin sensitization.…”
Section: The Integral Inflammasomesupporting
confidence: 58%
“…As the negative regulation of IL-1β by NLRP12 would effectively inhibit LC migration and DC accumulation, the presumption is that this mechanism would prevent the acquisition of skin sensitization. However, as NLRP12 is known to be required for the development of skin sensitization to certain allergens, it is postulated that there must be some, as yet unknown mechanism for the observed dependence upon NLRP12 (Arthur et al, 2010).…”
Section: Nlrp12mentioning
confidence: 99%
“…Other NLR family members have been suggested to regulate DC maturation or migration, such as NLRP3 and NLRP12, respectively (17,18). The mechanisms by which these NLRs regulate DC function have not been determined.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated local or systemic levels of IL-1β, associated with inappropriate inflammasome activity, have been reported in various diseases, particularly in allergic disorders (10)(11)(12). Furthermore, previous studies have reported that NLRP3, NLRP12 and absent in melanoma (AIM)2 are involved in different models of allergy (13)(14)(15). In addition, NLRP3 has been introduced as an important inflammasome in contact hypersensitivity (16) and allergic airway diseases (14,17).…”
Section: Elevated Caspase-1 Activity and Il-1β Expression Are Associamentioning
confidence: 99%